Magnetic heating across the cosmological recombination era: results from 3D MHD simulations. Issue 3 (7th July 2018) - Trivedi, Pranjal; Reppin, Johannes; Chluba, Jens; Banerjee, Robi
ABSTRACT: The origin of cosmic magnetic fields is an unsolved problem and magnetogenesis could have occurred in the early Universe. We study the evolution of such primordial magnetic fields across the cosmological recombination epoch via 3D magnetohydrodynamic numerical simulations. We compute the effective or net heating rate of baryons due to decaying magnetic fields and its dependence on the magnetic field strength and spectral index. In the drag-dominated regime (z ≳ 1500), prior to recombination, we find no real heating is produced. Our simulations allow us to smoothly trace a new transition regime (600 ≲ z ≲ 1500), where magnetic energy decays, at first, into the kinetic energy of baryons. A turbulent velocity field is built up until it saturates, as the net heating rate rises from a low value at recombination to its peak towards the end of the transition regime. This is followed by a turbulent decay regime (z ≲ 600) where magnetic energy dissipates via turbulent decay of both magnetic and velocity fields while net heating remains appreciable and declines slowly. Both the peak of the net heating rate and the onset of turbulent decay are delayed significantly beyond recombination, by up to 0.5 Myr (until z ≃ 600–700), for scale-invariant magnetic fields. We concentrate on low magnetic field strength to avoid confusion with magnetic field-generated density fluctuations. Analytic approximations are provided and we present numerical results for a range of field strengths (≃10 −3 − 2 × 10 −2 nG) and spectral indices, illustrating the redshift-dependence of dissipation and net heating rates. These can be used to study cosmic microwave background constraints on primordial magnetic fields.